RAWA PENING DALAM PERSPEKTIF POLITIK LINGKUNGAN: SEBUAH KAJIAN AWAL - Seftyono, Cahyo (Badan Pengembang Konservasi UNNES, 2014)
Rawa Pening is one of the swamp ecosystem which are important for not only the local residents of Ambarawa, Semarang, but also the communities in northern parts of Central Java. Rawa Pening as ecological systems has ability to allow water demarcation, so flood can be avoided during the heavy rain and a severe drought can be prevented when the dry season comes. Rawa Pening in the context of the natural sciences, is only limited to the physical existence of a 'puddle'. However, when it is observed further, then its existence is a part of a more complex system, which involves social-political actors. In this framework, the construction which is planned for Rawa Pening consequently involves values believed by local people. They are in relation to either culture, economy or politics. This study aims to reveal how Rawa Pening is seen from the point of view of environmental politics briefly. Rawa Pening is no longer viewed only as a water border, but also discourse space of public policy which involves the community, the state, and certainly, the ecosystem itself. Therefore, this study will describe Rawa Pening in the viewpoint of natural science, social science, and political economy, as well as political environment as a multidisciplinary study.Keywords: Rawa Pening, Local Communities, Environmental Politics Rawa Pening merupakan salah satu ekosistem yang penting bagi masyarakat, bukan saja bagi warga yang ada di daerah Ambarawa, Kabupaten Semarang, bahkan juga sebagian wilayah utara Jawa tengah. Rawa Pening menjadi sistem ekologi yang memungkinkan adanya sempadan air sehingga tidak menyebabkan banjir manakala datang hujan besar dan juga tidak ada musibah kekeringan yang parah manakala ada musim kemarau panjang. Rawa Pening dalam konteks ilmu alam, memang hanya sebatas pada keberadaan fisikal dari sebuah ‘genangan air’. Namun demikian, ketika dibaca lebih jauh, maka keberadaannya merupakan bagian dari sistem yang lebih kompleks, yang melibatkan aktor-aktor sosial-politik. Dalam kerangka ini, pembangunan yang ditujukan pada Rawa Pening mau tidak mau harus melibatkan nilai yang diyakini masyarakat lokal. Baik dalam kaitannya dengan nilai-nilai budaya, ekonomi maupun politik. Tulisan ini hendak membaca secara ringkas bagaimana Rawa Pening dilihat dari kaca mata politik lingkungan. Rawa Pening tidak lagi dilihat hanya sebagai sempadan air, melainkan juga ruang diskurus kebijakan publik yang melibatkan masyarakat, negara dan juga tentunya ekosistem itu sendiri. Oleh karenanya, tulisan ini akan mendeskripsikan Rawa Pening dalam sudut pandang sains, ilmu sosial, politik ekonomi, hingga politik lingkungan itu sendiri sebagai kajian yang multidisiplin.Kata Kunci: Rawa Pening, Masyarakat Lokal, Politik Lingkungan